OCEANS 2021: San Diego – Porto 2021
DOI: 10.23919/oceans44145.2021.9706046
|View full text |Cite
|
Sign up to set email alerts
|

Wireless radio link design to improve near-shore communication with surface nodes on tidal waters

Abstract: Wireless radio link design to improve near-shore ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…II due to higher flooding velocities in that part of the tidal cycle. Note also that previous work [7] has shown that centimeter-level differences in antenna height can have a significant impact on the channel characteristics.…”
Section: Environmental Dynamicsmentioning
confidence: 82%
“…II due to higher flooding velocities in that part of the tidal cycle. Note also that previous work [7] has shown that centimeter-level differences in antenna height can have a significant impact on the channel characteristics.…”
Section: Environmental Dynamicsmentioning
confidence: 82%
“…This section revisits the two-ray propagation model from the perspective of shore-to-shore (S2S) and shore-to-vessel (S2V) RF communication links subject to variations in the water surface level. A similar analysis has been presented before in the literature [23]- [27], but using a simplified version of the two-ray model, and without considering the impact of the intertidal zone. Thus, this section also discusses the geometrical aspects determining if the reflection point (from the two-ray model viewpoint) falls within the intertidal zone, and how this situation may influence the modeling approach.…”
Section: Two-ray Channel Modelmentioning
confidence: 85%
“…Despite some aspects of this phenomenon having been effectively described by the tworay model (e.g. [23]- [27]), further investigations on diverse environmental settings (e.g., estuaries and wetlands), using emerging communication technologies (e.g., LoRa) and/or incorporating precise tidal modeling methods, are still scarce.…”
Section: A Tidal Fadingmentioning
confidence: 99%
See 2 more Smart Citations